2017
DOI: 10.3847/1538-4365/aa96b0
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Synergy between LSST and Euclid

Abstract: Euclid and the Large Synoptic Survey Telescope (LSST) are poised to dramatically change the astronomy landscape early in the next decade. The combination of high-cadence, deep, wide-field optical photometry from LSST with highresolution, wide-field optical photometry, and near-infrared photometry and spectroscopy from Euclid will be powerful for addressing a wide range of astrophysical questions. We explore Euclid/LSST synergy, ignoring the political issues associated with data access to focus on the scientifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 108 publications
(143 reference statements)
2
46
0
2
Order By: Relevance
“…In fact, it seems that since the Balmer break is so important as we have shown that following it into the infrared regime is essential to improve LSST photometric redshifts. This is in line with previous work highlighting the potential photometric redshift improvement from combining LSST observations with infrared data from future space telescope missions ( Rhodes et al 2017;Graham et al 2019). In a future paper we will look at how much information is gained from adding infrared and UV filters as well as what optimal filters in these wavelengths designed to complement LSST would look like.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, it seems that since the Balmer break is so important as we have shown that following it into the infrared regime is essential to improve LSST photometric redshifts. This is in line with previous work highlighting the potential photometric redshift improvement from combining LSST observations with infrared data from future space telescope missions ( Rhodes et al 2017;Graham et al 2019). In a future paper we will look at how much information is gained from adding infrared and UV filters as well as what optimal filters in these wavelengths designed to complement LSST would look like.…”
Section: Discussionsupporting
confidence: 92%
“…The most immediate impact of overlap between the LSST DDFs and WFIRST and Euclid Deep Fields will be improved photo-z scatter at the 20% (Graham et al 2018 in prep.) to 50% level [11] from 0.3 < z < 3.0. The improved DDF photo-z estimates will be critical for training photoz estimates in the WFD survey, where the wide Euclid NIR coverage region is too shallow to significantly improve LSST photo-z on its own.…”
Section: Scientific Motivationmentioning
confidence: 99%
“…These two sets correspond to an LSST-like optical survey (Ivezić et al 2019), and the same survey with additional Euclid-like infrared observations (Laureijs et al 2011). The complementarity of LSST and Euclid has been investigated previously (e.g., Rhodes et al 2017); additional filter bands will help to break colour-redshift degeneracies and therefore enable more accurate photometric redshifts. Simulated observations are generated by redshifting a template, integrating over the relevant filter response curves, scaling the results to a given i-band magnitude, adding observational noise and imposing selection criteria.…”
Section: Tests On Simulated Sourcesmentioning
confidence: 98%